A Effect of Maltodextrin Concentration on Antioxidants Activity and Stability of Natural Coloring Powder of Secang Wood (Caesalpinia Sappan L) in Various Conditions of Ph and Temperature - Huswatun Hasanah; Daimon Syukri; Ismed Ismed (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
This research was aimed to determine the effect of different concentrations of maltodextrin on antioxidants and stability of the natural dye powder of sappan wood under various pH and temperature conditions. This study used a completely randomized experimental design with five treatments and three replications. The treatments in this study were: A (addition maltodextrin 5%), B (addition maltodextrin 10%), C (addition maltodextrin 15%), D (addition maltodextrin 20%), and E (addition maltodextrin 25%). Before the drying process, maltodextrin was added to the sappan wood extract that had been created. Yield, color analysis, solubility test, color stability test based on pH and heating temperature fluctuations, water content, and antioxidant activity are among the observations made. The addition of maltodextrin had a substansial impact on yield, and color the addition of maltodextrin had a substantial impact on yield, color analysis, solubility, water content, and antioxidant activity, according to the findings. The best treatment in this study was treatment A (addition maltodextrin 5%) with the characteristics of yield 18.33,%, hue value in color analysis was 39,58%, with yellow red color, solubility 87,33%, water content 6,83, and 17,80 ppm antioxidant activity (strong category), as well as maltodextrin which was stable against various pH and temperature treatments. Keyword: sappan wood, maltodextrin, antioxidant activity, color stability.